Characterization of Biodiesel from residual friture oil, sunflower, through the ethanolic base transesterification process - Hugo Jimenéz-Pacheco (2019)
The conservation of the environment is becoming a global concern for the use of fuels from fossil waste, and the production of biodiesel from renewable sources is being considered as an eco-friendly alternative since oleaginous organic waste presents potential as Energy condition.An important aspect is to minimize the impacts generated by this waste under different conditions, and an operation related to the aspect is the elaboration and comparison of biodiesel obtained from residual frying oils with biodiesel produced with sunflower oil through the transesterification process based on ethanol. The evaluation was carried out on a laboratory scale with parameters and specifications found in the Peruvian Technical Standard for Biodiesel (NTP- 321.12-200-2008), with the exception of water content, and the oxidative stability index (IEO).The following results were obtained 739.7 mg / kg and 1.5 hours and these do not meet the standards whose minimum reference corresponds to 500 mg / kg and 3 hours, respectively. The yield of residual oil and sunflower corresponds to 68.5% and 85.2% respectively. The research work establishes that the production of biodiesel from residual frying oil by the ethanol-based transesterification process is significantly less than the process with sunflower oilseeds, showing greater performance and stability.